Post-processing of black soldier fly larvae frass and palm oil fuel ash for organic fertilizer production - Leong, Brandon Xeyn Hin (2024)

(untitled)
Inadequately managed biodegradable waste poses a significant environmental, social, and economic hazard, prompting the need for comprehensive waste management strategies. In recent decades, significant attention has been directed towards waste management and valorization efforts, aiming to develop integrated and sustainable waste management approaches. The utilization of black soldier fly larvae (BSFL) for waste treatment has gained traction, offering a pathway to convert waste into marketable goods and foster circularity within the ecosystem. BSF larvae demonstrate voracious feeding habits on a variety of organic waste streams, including food scraps and agro-industrial residues, significantly reducing waste volume in a shorter timeframe compared to traditional composting methods. Among the byproducts generated, frass, the residue of BSF larvae rearing, has garnered interest due to its nutrient-rich composition, positioning it as a potential organic fertilizer. However, the rapid composting process render it biologically unstable, necessitating post-treatment measures for stabilization to enhance its suitability as a fertilizing amendment. Alternatively, blending frass with other fertilizer products could enhance matrix stabilization and augment the effectiveness of the combined fertilizer. The initial analysis of raw frass indicates a high value in nutrient composition of approximately 3.5% nitrogen, 1.1% phosphorus, 3% potassium, but with a low carbon-to-nitrogen ratio of 12 to 1. To address the low C/N ratio of fresh frass, it is blended with palm oil fuel ash, a biowaste rich in carbon, and composted to achieve an optimal C/N ratio and nutrient enhancement. Subsequent analysis of the compost reveals an increased C/N ratio (22:1) and phosphorus content (2.3%). However, there is a notable decrease in nitrogen content to 1%, suggesting nitrogen loss during the composting process. This study evaluates BSF larvae frass’s potential as an organic fertilizer for sustainable cultivation, aiming to create a well-balanced fertilizer by incorporating palm oil fuel ash into the frass-based fertilizer to meet specific crop nutrient requirements